Association Between Total Cell Free DNA and SARS-CoV-2 In Kidney Transplant Patients: A Preliminary Study - Reusing, Jose Otto; Yoo, Jongwon; Desai, Amishi; Brossart, Katya; McCormick, Sarah; Malashevich, Allyson Koyen; Bloom, Michelle S.; Fehringer, Gordon; White, Roseann; Billings, Paul R.; Tabriziani, Hossein; Demko, Zachary P.; et al. (Transplantation proceedings, 2022)
Kidney transplant (KT) recipients are at high risk for developing severe COVID-19. Lowering immunosuppression levels in KT recipients with COVID-19 encourages native immune responses but can raise the risk of rejection. Donor-derived cell-free DNA (dd-cfDNA), reported as a fraction of total cfDNA, is a proven biomarker for KT rejection. Total cfDNA levels are elevated in patients with COVID-19, which may depress dd-cfDNA fractions, potentially leading to missed rejections. A retrospective analysis of 29 KT recipients hospitalized with COVID-19 between April and November 2020 examined total and dd-cfDNA levels. Blood samples were collected after onset of COVID-19, with follow-up samples collected from a subset of patients, when infection had likely subsided. After COVID-19 diagnosis, the median total cfDNA level was elevated (7.9 multiples of median [MoM]). A significant decrease in total cfDNA levels was observed between the first and second time points (6.2 MoM, 1.0 MoM; P <001). A significant positive association was identified between total cfDNA levels and COVID-19 severity (P = .02; R2 = .19). Two patients with biopsy-proven acute cellular rejection had dd-cfDNA fractions below the 1% cutoff for rejection (0.20% and 0.78%), with elevated total cfDNA levels of 7.9 MoM and 41.8 MoM, respectively. In this preliminary study, total cfDNA levels were elevated in KT patients with COVID-19, subsiding after resolution of infection. High total cfDNA levels may confound dd-cfDNA results, leading to failure to identify rejection. Considering total cfDNA levels is important in interpretation of dd-cfDNA tests for assessment of rejection in KT patients with COVID-19 or other infection.